1998
DOI: 10.1007/bf03189820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of d-limonene on the transdermal penetration of felodipine

Abstract: Felodipine is a calcium antagonist, one of the dihydropyridines, with potential application in transdermal therapeutic systems (TTS). Earlier studies reported that the high lag time of this drug limited its potential development in a TTS. The present study analyzes the effect of d-limonene at concentrations of 0.5, 1, 5 and 10% on the transdermal penetration of this drug. The study was performed using a diffusion technique in vitro, with the skin of the hairless rat. d-Limonene significantly reduced the lag ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…Thus, we decided to continue with PG, OA and L at concentrations that give physically stable formulations (Table II). Previous studies on similar topics also helped us to confirm concentrations of selected penetration enhancers [10,34]. We also saw that OA and L were physically incompatible with G and OC, respectively.…”
Section: Ex Vivo Skin Permeation and Penetration Studysupporting
confidence: 60%
“…Thus, we decided to continue with PG, OA and L at concentrations that give physically stable formulations (Table II). Previous studies on similar topics also helped us to confirm concentrations of selected penetration enhancers [10,34]. We also saw that OA and L were physically incompatible with G and OC, respectively.…”
Section: Ex Vivo Skin Permeation and Penetration Studysupporting
confidence: 60%
“…17 However, other in vitro studies reported no appreciable differences in transdermal penetration of certain drugs when d -limonene was used between 1% and 10% concentrations. 18…”
Section: Discussionmentioning
confidence: 99%
“…17 However, other in vitro studies reported no appreciable differences in transdermal penetration of certain drugs when d-limonene was used between 1% and 10% concentrations. 18 The reaffirmation of a lack of significant human skin penetration of d-limonene is also interesting in light of the use of d-limonene as a penetration enhancer of various chemicals. 19,20 However, the percutaneous enhancing properties of limonene depend on its interaction with compounds such as propylene glycol and in most cases, penetration enhancement has been documented at levels (usually greater than 5%) that are much higher than those used in fragrance and cosmetic uses (maximum level 3.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of d-limonene in the felodipine transdermal formulation has produced an increase in the permeability of the drug through skin 34 .…”
Section: D-limonenementioning
confidence: 99%